(untitled) (Semiárida, 2020)
Irearing beef heifers in Rio Grande do Sul has been performed, mostly, in natural grasslands. This category has considerable nutrition requirements when mating at 24 monthswas proposed. This could need adjustment of grazing intensity to provide gains required for this category. The aim of this work was to characterize and to analyze possible relations not apparent, through of meta-analysis, with livestock data from nine experiments performed with heifers between seven and 26 months of age. Analyzed variables were carrying capacity(CC), average daily gain (ADG) and live weight gain per area (GPV). Data were transformed vectorially by standardizing by the range and submitted to multivariate analyzes of cluster and ordination using Euclidean distance as a measure of similarity. Cluster analyzes showed five groups of sampling units (p=0.02). ADG was the variable with highest correlation (R=0.98) with axis I, which explained most of data variation (64.27%). CC was the variable most correlated (R=0.98) with axis II, which explained 32.24% of results. The GPV was in the intermediate position it being 74.15% and 57.26% related to the axes I and II, respectively. From analyzed variables, ADG was the variable that explained most of data’s variability.